Heidegger's Children. - Wolin, Richard (Princeton University Press, 2015)
Martin Heidegger is perhaps the twentieth century's greatest philosopher, and his work stimulated much that is original and compelling in modern thought. A seductive classroom presence, he attracted Germany's brightest young intellects during the 1920s. Many were Jews, who ultimately would have to reconcile their philosophical and, often, personal commitments to Heidegger with his nefarious political views. In 1933, Heidegger cast his lot with National Socialism. He squelched the careers of Jewish students and denounced fellow professors whom he considered insufficiently radical. Fo.